Impact of HR Management on AI Implementation and Data Protection in Indonesian Manufacturing - Achmad Rozi; Junengsih Junengsih; Surya Alam; Avinash Pawar; Wahid Sumarjo; Denok Sunarsi (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2026)
This study aims to analyze the influence of Human Resource Management (HRM) strategies on the implementation of Artificial Intelligence (AI) in industrial forecasting and data protection within the cybersecurity era in Indonesian manufacturing companies. A quantitative approach was used with a survey method to collect data from 96 employees of manufacturing companies in Indonesia, determined by the Lemeshow formula. The findings show that HRM strategy has a positive and significant effect on industrial forecasting, with a t-statistic of 48.639 > 1.984 and a P-value of 0.000 < 0.05. Furthermore, HRM strategy significantly affects data protection, with a t-statistic of 27.927 > 1.984 and a P-value of 0.000 < 0.05. Industrial forecasting positively influences AI implementation, with a t-statistic of 27.927 > 1.984 and a P-value of 0.000 < 0.05, while data protection also positively affects AI implementation, supported by a t-statistic of 2.457 > 1.984 and a P-value of 0.014 < 0.05. Additionally, HRM strategy significantly influences AI implementation, with a t-statistic of 6.020 > 1.984 and a P-value of 0.000 < 0.05. Finally, HRM strategy positively impacts AI implementation through data protection, indicated by a t-statistic of 2.421 > 1.984 and a P-value of 0.016 < 0.05. In conclusion, this study highlights the importance of HRM strategies in enhancing AI implementation and cybersecurity in Indonesian manufacturing companies, underscoring the need for integrating HR strategies with AI and data protection systems to optimize operational efficiency and safeguard against cyber threats.